Vertical Shaking Accident and Cause Investigation of 39-story Office Building. Issue 3 (1st September 2016) - Chung, Lan; Park, Taewon; Woo, Sung Sik
Abstract : At around 10 a.m. on July 5, 2011, a building shaking occurred at Techno Mart 21 located in Guui-dong, Seoul, for 10 to 15 minutes, resulting in emergency evacuation of the residents. Because this building is a 39-story building, evacuation from the upper floors took a long time. In the initial phase of the accident, the building structure was determined to be safe through an emergency safety evaluation conducted by the Korea Infrastructure Safety Corporation operated by the Korean government. Such social anxiety was further amplified by speculative reports released to the press regarding footing settlement, wind-induced vibration and climate-induced vibration prior to a review of the vibration source by an expert group. Thus, the need to discover the vibration source and to present a solution was suggested. The purpose of the study was to conduct an initial investigation on the vibration source, identify the exact cause of the vibration through an investigation into the predicted vibration source and structural analysis, and establish the appropriate measures to prevent recurrence of such accidents.